(untitled) (Modern education and development, 2024)
Maqolada Kompyuter grafikasining evolusiyasini chuqur o’rganish va texnologiyalarining tasvir yaratish jarayonlaridagi rolini o’rganadi. Shuningdek zamonaviy trend darajasiga erishgan kompyuter grafikasining tehnologiyalarini o‘rganadi. The article provides an in depth study of the evolution of computer graphics and explores the role of technology in image processing. Studies the technologies of computer graphics that have reached the modern development trend.